Estudo das propriedades físicas e mecânica com análise microestrutural da liga níquel-titânio processada por metalurgia do pó - Oliveira Filho, Luiz Gastão de (2019)
The Nickel-Titanium alloy (NiTi) belongs to the group of so-called intelligent materials, being outstanding due to its excellent shape memory, superelasticity, damping and biocompatibility properties. This alloy applies both in the technological areas and especially, in the medical and dental areas. The characteristic of the shape memory effect, one of the most important, can be explained by the phase transformations associated with the martensitic (B19') and austenitic (B2) phases, which also allow the appearance of the superelastic phenomenon. This work proposes a microstructural analysis and the physical and mechanical properties of NiTi alloy processed through powder metallurgy, combining temperature and time to produce a smaller volume of secondary phases and to obtain the structure with the predominance of the martensitic phase. The sintering of the alloy was combined over the course of 12, 24 and 36 hours at a temperature of 932 °C without the presence of the liquid phase. This work includes techniques of characterization by X-Ray Diffraction (XRD), Energy Dispersive X-ray Fluorescence Spectroscopy (EDX), Energy Dispersive X-Ray Spectroscopy (EDS); mechanical property by Vickers microhardness; physical properties analyzed by density and porosity; and, lastly, metallography technique with the aid of Optical Microscopy (OM) and Scanning Electron Microscopy (SEM). The results showed the existence of the austenitic (B2) and martensitic (B19') phases of the alloy, as well as the secondary phase of NiTi 2 and Ni 2 Ti 4 O oxide, and the sintering time caused changes in the structure of the sintered ones. It was observed that with increasing sintering time: the porosity decreases, resulting in a volumetric shrinkage and in the density increase; the NiTi 2 phase may decrease, resulting in the transfer to B2 and B19' phases; the secondary phase is not eliminated; and there is no direct relationship with the microhardness, but with the phases present in the alloy, being associated with B2 phase with a higher microhardness and B19' with a lower microhardness. Therefore, the sintering for 24 h has been shown to be the most ideal route, due to the predominance of the martensite phase, which can result in an alloy with the best properties of shape memory effect.